Bureau of the Centre for the Study of Surrealism and its Legacy - Dion, Mark; David Lomas; Dezeuze, Anna; Kelly, Julia (London; Bookworks, 2018)
Texts: Anna Dezeuze, Julia Kelly and David Lomas.
English
Keywords: N4390-5098 Visual Arts. Exhibitions